Impacto de vizinhança e área de influência direta : implicações na Região Metropolitana da Grande Vitória - Souza, Susie Fonseca de (2019)
It is the Neighborhood Impact Study, a proposed instrument for the purpose of analyzing previously the positive and negative impacts of an enterprise or activity, to be implemented in the urban environment. That said, we started the reflection on the righ